Fate of pioneering vegetation patches in a dynamic meandering river. Issue 8 (10th March 2019) - Kleinhans, Maarten; Douma, Harke; Addink, Elisabeth A.
Abstract: Fluvial biomorphodynamics in actively meandering rivers entail interactions between hydromorphodynamics and pioneering tree species that have eco‐engineering effects. Here we study spatiotemporal patterns of vegetation patches smaller than 150 m 2 in a 4 km reach of the river Allier in France in order to unravel causes for tree persistence and mortality and identify spatial trends across the river valley. To this end we analysed aerial photographs by object‐based image analysis over a period of 56 years and tracked individual patches through time. Furthermore the cover and surface age of the study reach were classified. The large‐scale shifts of channels, bars and vegetation are consistent with the meandering process and chute cutoffs. However, the spatiotemporal patterns of the vegetation patches are surprising in that they are ubiquitous and have ages up to decades on the highly dynamic meander belt, but hardly expand into larger vegetation patches. Patches disappear exponentially as a function of their age, and faster so in the last decades. Causes are amalgamation into the riparian forest flanking the meander belt and mortality likely due to desiccation or erosion. Patches have a higher probability of survival when further away from the active channel and closer to high vegetation patches and valley boundary. The window of opportunity of vegetation settlement widens towards the valley boundaries and in floodplain lows of former channels and chutes. These results imply a gradual cross‐valley gradient of riparian vegetation settling, survival and succession. © 2019 The Authors. Earth Surface Processes and Landforms Published by John Wiley & Sons Ltd. Abstract : Small isolated pioneer vegetation patches in a dynamic meandering river have a suprisingly long survival time but hardly expand. Their dynamics are quantified for 56 years for the Allier River in France by Object‐Based Image Analysis applied to aerial photography.